Caprellidae - Guerra-García, José M.; Lowry, J. K. (Zootaxa, 2009)
Seventeen species of caprellids in 14 genera are reported, mainly from Lizard Island on the Great Barrier Reef, Queensland, Australia. Metaprotella sandalensis Mayer, 1898 and Quadrisegmentum triangulum Hirayama, 1988, are the most common species in the reef system. Although caprellids were present at most sites, they were abundant only on hydroid and sediment substrates.